Carbon Nano Compound from Seeds: Methodology to Obtain a High Added Value Product - M.G. Fonseca; L.N. Batista; V.F. Silva; T.C. Soares; G. Alves Romeiro (Chemical Engineering Transactions, 2014)
The use of a green chemistry is the philosophy proposed by this work. Development of new energy sources has been developed by many research groups around the world. A high added value product, a carbon adsorbent is the main result of this work. This work was initiated through the drying seeds process. After this stage, oil from the seeds was extracted by hexane by Soxhlet extraction. This process produces two main products. The oil that in general is useful to produce biodiesel and the solid tart. Tart was used to produce charcoal by a low temperature pyrolysis process, at 380°C under nitrogen atmosphere. From this technique were obtained initially four energy sources: Charcoal, gas, pyrolysis oil and water. The charcoal was heated in a muffle furnace at different temperatures range from 500°C to 1,000 °C. This stage was realized in attempt to obtain a most pure charcoal, with higher carbon value. The analysis of Raman spectroscopy and solid NMR show that the best char was obtained at 600°C temperature. By Raman spectroscopy was observed that in higher temperatures were obtained aggregated products and by solid NMR that the products really are good conductors. Charcoal was even characterized by SEM and EDS. After product characterization, was tested the methylene blue adsorption capacity of the obtained material by UV analysis. Results of UV analysis show a great adsorption capacity.